2020
DOI: 10.37536/ej.2020.28.1915
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of English Teachers About the English Lessons in the Current Education System of Turkey

Abstract: This study aims to clarify the perceptions of English teachers who work in private schools or state schools about the English lessons in the current education system. By using a questionnaire, data was collected from 35 English teachers; 16 of them were state school English teachers and 19 of them were working at different private schools. Data derived from the participants were analyzed by using SPSS. In the light of the results, the perceptions of the English teachers were presented in relation to the items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The participants were evaluated on various items related to the English lessons taught in government schools and private schools. The findings revealed that the English teachers working at different schools have more positive attitudes about the English lessons taught by the public schools (Gunes, 2020). The respondents for the current study agreed with the role of the school to support English language learning, while in the previous studies by IIdikut, Kutlu & Akman (2021) and Gunes (2020).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The participants were evaluated on various items related to the English lessons taught in government schools and private schools. The findings revealed that the English teachers working at different schools have more positive attitudes about the English lessons taught by the public schools (Gunes, 2020). The respondents for the current study agreed with the role of the school to support English language learning, while in the previous studies by IIdikut, Kutlu & Akman (2021) and Gunes (2020).…”
Section: Discussionsupporting
confidence: 58%
“…According to IIdikut, Kutlu & Akman (2021), the teachers are focusing more on the learners' motivation to provide more positive results in English language learning and that was found more in private schools. Also, this is in line with study by Gunes (2020) they aimed to investigate the perceptions of English teachers regarding the English lessons taught in public schools and private schools. The participants were evaluated on various items related to the English lessons taught in government schools and private schools.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation